Hydraulic fracturing and well stimulation - Aminzadeh, Fred (Wiley ; Scrivener Publishing, 2019)
Hydraulic fracturing (or "fracking") has been a source of both achievement and controversy for years, and it continues to be a hot-button issue all over the world.' It has made the United States an energy exporting country once again and kept the price of gasoline low, for consumers and companies.' On the other hand, it has been potentially a dangerous and destructive practice that has led to environmental problems and health issues.' It is a deeply important subject for the petroleum engineer to explore as much as possible. This collection of papers is the first in the series, Sustainable Energy Engineering, tackling this very complex process of hydraulic fracturing and its environmental and economic ramifications.' Born out of the journal by the same name, formerly published by Scrivener Publishing, most of the articles in this volume have been updated, and there are some new additions, as well, to keep the engineer abreast of any updates and new methods in the industry. Truly a snapshot of the state-of-the-art, this groundbreaking volume is a must-have for any petroleum engineer working in the field, environmental engineers, petroleum engineering students, and any other engineer or scientist working with hydraulic fracturing